2021
DOI: 10.3390/clinpract11040093
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Delta Variant B.1.617.2 COVID-19

Abstract: With the delta variant of COVID-19, known as B.1.617.2, quickly ramping up infections around the world, we need to understand what makes this variant more contagious. One study has reported that the delta variant is 60% more transmissible than the alpha variant. As of August 2021, the delta variant has quickly become the dominant strain. Despite countries like the US, where most of the population is vaccinated, COVID-19 has made a resurgence in infections. Collectively, as a country, we ask: is it more deadly?… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
191
0
7

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 243 publications
(223 citation statements)
references
References 18 publications
4
191
0
7
Order By: Relevance
“…Currently, the Delta variant has been the most frequent variant circulating globally ( 14 ). Indeed, national genomic surveillance of SARS-CoV-2 variants has identified the Delta variant as the most dominant circulating variant in Indonesia (97.8%), followed by Alpha (1.7%) and Beta variants (0.5%) ( 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the Delta variant has been the most frequent variant circulating globally ( 14 ). Indeed, national genomic surveillance of SARS-CoV-2 variants has identified the Delta variant as the most dominant circulating variant in Indonesia (97.8%), followed by Alpha (1.7%) and Beta variants (0.5%) ( 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…Although specific mutations in the spike protein, including the B.1.1.7 and B.1.351 variants, are generally effectively neutralized by existing vaccines [ 85 ], the response of vaccines to other variants, including the P.1 andB.1.617.2 display significantly reduced neutralization of SARS-CoV-2, with other variants such as the B.1.1.529 posing as novel challenges toward herd immunity. The B.1.617.2 variant, initially identified in India [ 89 ], possesses mutations granting enhanced transmissibility and producing more severe symptoms characteristic of higher viral loads within the respiratory tract, in addition to a unique symptom of gangrene secondary to severe blood clots. The anti-inflammatory effects of PAD inhibitors in combination with immunothrombosis suppression through NET inhibition offer a potential acute treatment for severe SARS-CoV-2 patients in whom vaccine protection is breached, in the case of more resistant strains.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, this variant is more contagious than previous variants of SARS-CoV-2. Meanwhile, the first data showed that the people infected with the omicron variant present with milder infection and are mainly young and middle-aged (Meo et al 2021 ; Shiehzadegan et al 2021 ; Wang and Han 2022 ).…”
Section: Hand Eye Hygiene Personal Protective Equipment and Social Di...mentioning
confidence: 99%